Knowledge and attitude of dentists toward minimally invasive caries management in Almadinah Almunawwarah province, KSA - Amnah A. Algarni, PhD; Raghad M. Alwusaydi, BDS; Raghad S. Alenezi, BDS; Nada A. Alharbi, PhD; Soha F. Alqadi, DDent (Journal of Taibah University Medical Sciences, 2024)
الملخص: أهداف البحث: يتم تحويل إدارة تسوس الأسنان نحو طب الأسنان طفيف التوغل، واستراتيجيات أكثر تحفظا وقائمة على الأدلة. على الرغم من أن معظم مدارس طب الأسنان تبدأ في دمج استراتيجيات إدارة تسوس الأسنان طفيفة التوغل في مناهجها الدراسية؛ ليس معروفا جيدا ما إذا كان يتم تنفيذها في الممارسة اليومية. هدفت هذه الدراسة إلى تقييم معرفة وموقف أطباء الأسنان العاملين في منطقة المدينة المنورة في المملكة العربية السعودية فيما يتعلق بتطبيق طب الأسنان طفيف التوغل في إدارة تسوس الأسنان. طريقة البحث: أجريت دراسة مقطعية باستخدام استبانة إلكترونية بين أطباء الأسنان الممارسين في كل من العيادات الخاصة والعامة في المدينة المنورة، المملكة العربية السعودية. تتكون الاستبانة من 4 أقسام بما في ذلك البيانات الديموغرافية وتعليم الأسنان والخبرة السريرية والمعرفة والموقف فيما يتعلق بطب الأسنان طفيف التوغل وإدارة تسوس الأسنان. بالنسبة للتحليل الإحصائي، تم حساب إحصائيات وصفية بسيطة مثل التوزيعات المتوسطة والترددية؛ بينما تم إجراء المقارنات باستخدام اختبار كاي سكوير. النتائج: شارك في الدراسة ما مجموعه 130 طبيب أسنان، غالبيتهم من أطباء الأسنان السعوديين العامين العاملين في عيادات الأسنان الخاصة مع توزيع مماثل بين الذكور والإناث الذين تتراوح أعمارهم بين 25 و 35 سنة. فيما يتعلق بمعرفة إزالة التسوس الانتقائي، اختار 20 ٪ فقط أن إزالة التسوس الانتقائي يعتمد على عمق الآفة، بينما أجاب 74.6 ٪ أن تناسق الأسنان الملتهب مهم لإزالة التسوس الانتقائي. على الرغم من أن 60٪ كشفوا أنهم سيقيمون مخاطر تسوس المريض قبل بدء العلاج، إلا أن 11.5٪ فقط سيقومون بتقييم المخاطر والعلاج غير الجراحي في الزيارة الأولى لإدارة التسوس. يستخدم 4.6٪ فقط معايير النظام الدولي للكشف عن التسوس وتقييمه 2 في تشخيص تسوس الأسنان، بينما يستخدم 46.2٪ معايير ''جي في بلاك''. بالإضافة إلى ذلك، وافق 53.8٪ من المشاركين على أنه يجب إزالة التسوس بالكامل لوقف تقدم التسوس. الاستنتاجات: حصل أطباء الأسنان في المدينة المنورة على معرفة معقولة فيما يتعلق بأهمية طب الأسنان طفيف التوغل في إدارة تسوس الأسنان، لكنهم لا يطبقون بشكل كامل مفاهيم مثل تقييم مخاطر التسوس ومعايير تشخيص تسوس الأسنان الموصى بها مؤخرا في الممارسة السريرية اليومية. Abstract: Objective: Over time, the management of dental caries has shifted towards minimally invasive dentistry (MID) and more conservative and evidence-based strategies. Although most dental schools have begun to incorporate MID caries management strategies in their curriculum; it has yet to be established whether these strategies are being implemented in everyday practice. In this study, we aimed to evaluate the knowledge and attitude of dentists working in Almadinah Almunawwarah province in KSA with regards to the implementation of MID in caries management. Methods: This was a cross-sectional study which involved sending a self-administered and anonymous questionnaire to dentists practicing in both private and public clinics in Almadinah Almunawwarah, KSA. The questionnaire consisted of four sections: demographic data, dental education, clinical experience, and knowledge and attitude with regards to MID and the management of caries. For statistical analysis, we calculated simple descriptive statistics, including mean and frequency distributions; comparisons were performed using the Chi-squared test. Results: A total of 130 dentists participated in the study; the majority of respondents were Saudi general dentists working in private dental clinics; there was a similar distribution of males and females and the age of the dentists ranged from 25 to 35 years. With regards to knowledge relating to selective caries removal (SCR), only 20% of subjects responded that SCR is based on lesion depth, while 74.6% reported that carious dentin consistency is important for SCR. Although 60% of respondents reported that they would assess a patient's risk of caries before commencing treatment, only 11.5% would perform risk assessment and non-surgical treatment in the first visit for caries management. Only 4.6% reported that they used the International Caries Detection and Assessment System (ICDAS) II criteria for the diagnosis of caries while 46.2% used the G.V. Black criteria. In addition, 53.8% of participants agreed that caries must be completely removed to prevent the progression of caries. Conclusion: Dentists in Almadinah Almunawwarah province had reasonable levels of knowledge regarding the importance of MID in caries management. However, they did not fully implement certain concepts, such as caries risk assessment and the recently recommended criteria for the diagnosis of caries, in their everyday clinical practice.